The Role of the Arabic Language in Developing and Enhancing the Function of Accounting Communication (A Historical-Professional Study) - Al-Nakib, Associate Professor Dr. Kamal Abdul Aziz Al-Nakib; Zgair, Assistant Professor Dr. Lutfy Jabar Zgair; Haider, Associate Professor Dr. Ibrahim Khalil Haider (Sulaimani Journal for Humanities, 2026)
This research paper is trying to investigate the role of Arabic language on enhancing and applying on the accounting communication function as it’s one of two main accounting functions. As the language consider as an effective communication tool for transforming the information into different forms one of them is writing skill to use to prepare the financial statements, some accounting sheets, and records. Within the last few decades this issue became more complicated by the influences of using the Artificial Intelligence techniques (AI) and using the natural language based on the nervous new-works as one of the main parts and types of (AI). The statement problem of this research is to answer the following main question, which is: Is there any clear role of effecting the Arabic language on enhancing and applying the accounting communication function? By answering this question will explore the importance of this research to show the relation between the humanities sciences and social sciences. The researchers have been designed the main negative hypotheses, which is there’s not any impact of Arabic language on enhancing and applying the accounting communication function, as they are using two variables, one of them is the independent variable as the Arabic language, and the 2nd’ one is the dependent variable, which is the accounting communication function. And finally, the researchers come out to some conclusions such as the Arab researchers added some valuable contributions on the accounting thought development and its applied sides one of them was the applying the accounting communication function accounting communication function accordingly one of main recommendations was to encourage the new researchers to take a part of designing an accounting theory based on Islamic thought approach.
Keywords: Arabic language; accounting; language development; accounting communication